Analysis of Spur Cylindrical Gear Pair Vibration Characteristic Considering Error and Randomness of Tooth Surface Friction - Zaida Gao; Shengbo Li; Shengping Fu; Polyakov Roman (Jixie chuandong)
Aiming at the problem of gear vibration characteristics with considering the error and randomness of tooth surface friction parameters are not clear. Combined with statistical methods and concentrated mass methods， the numerically study of the random characteristics of errors and tooth surface friction parameter is carried out. The influence of gear tooth errors on tooth surface friction parameters is analyzed. The bending-torsional coupled vibration model of a spur gear transmission is established in consideration of error and randomness of the tooth surface friction parameters. The fourth-order Runge-Kutta method is used for numerical solution， the vibration response of the gear transmission is obtained. The influences of gear error and the random tooth surface friction parameters on gear vibration responses are explored. The results show that the dynamic responses of the gear pair have more complicated randomness in the frequency domain and phase diagram under the collective effects of the error and the random tooth surface friction. However， error randomness interferes more with the dynamic stability of the gear system. And the research results provide a theoretical reference for the dynamic design of the gear transmission.